2013
DOI: 10.3176/tr.2013.4.08
|View full text |Cite
|
Sign up to set email alerts
|

Test-Taking Effort as a Predictor of Performance in Low-Stakes Tests

Abstract: We studied how time measures can be used as predictors of test-taking performance in low-stakes tests. Our sample consisted of undergraduate students (N = 327) who took a computer-based cognitive abilities test. Our aim was to find how test-takers' motivation manifests itself in test-taking effort. We found that a high test-taking speed is related to low test scores (the correlation between test score and Response Time Effort was r = .71). Also, the mean time for wrong answers per item was smaller than the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Such a pattern was quite consistent with the answers that the students had already given to the achievement goal showed disagreement or neutrality almost in all the items was higher than the low-stakes group. On the other hand, the result was consistent with the expectancy theory of motivation when higher probability of success (Silm et al, 2013) leads to more engagement for achieving the goals. In this study, when doing course assignments and classroom activities lower the stakes of the test and increase the chance of success, students in the low-stakes exam situation, students become more involved in academic, social, or extracurricular activities and is considered crucial for achieving positive academic outcomes and preventing dropping out (Finn, 1989;Connell and Wellborn, 1991).…”
Section: Discussionsupporting
confidence: 80%
“…Such a pattern was quite consistent with the answers that the students had already given to the achievement goal showed disagreement or neutrality almost in all the items was higher than the low-stakes group. On the other hand, the result was consistent with the expectancy theory of motivation when higher probability of success (Silm et al, 2013) leads to more engagement for achieving the goals. In this study, when doing course assignments and classroom activities lower the stakes of the test and increase the chance of success, students in the low-stakes exam situation, students become more involved in academic, social, or extracurricular activities and is considered crucial for achieving positive academic outcomes and preventing dropping out (Finn, 1989;Connell and Wellborn, 1991).…”
Section: Discussionsupporting
confidence: 80%
“…In PISA 2015, a shift from the paper-based assessment to a computer-delivered assessment has been implemented across the vast majority of participating countries. This enables the measure of new and expanded aspects of the domain constructs (OECD 2017), and also allows to use response time as a measure of test-taking effort to investigate the effect of motivation on persistence for future studies (e.g., Setzer et al 2013;Silm et al 2013;Wise and Kong 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As for evaluating the thresholds using percentage of correct scores, examinees were expected to provide fewer accurate responses under rapid-guessing than under effortful problem solving. In fact, earlier studies consistently found the proportion of correct scores under solution behavior to be substantially higher than the proportion under rapid-guessing (Lee and Jia 2014;Silm et al 2013;Wise and Kong 2005). Wise and Kong (2005) and Wise (2006) found that examinees who responded in an unreasonably short amount of time provided correct responses at a frequency similar to the frequency of yielding a correct response by random chance, where random chance was operationalized as the reciprocal of the number of response options (e.g., one out of four, or .25 for a multiple-choice item with four response options).…”
Section: Evaluating Thresholdsmentioning
confidence: 95%